2021
DOI: 10.3390/genes12040477
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporins in Cereals—Important Players in Maintaining Cell Homeostasis under Abiotic Stress

Abstract: Cereal productivity is reduced by environmental stresses such as drought, heat, elevated CO2, salinity, metal toxicity and cold. Sometimes, plants are exposed to multiple stresses simultaneously. Plants must be able to make a rapid and adequate response to these environmental stimuli in order to restore their growing ability. The latest research has shown that aquaporins are important players in maintaining cell homeostasis under abiotic stress. Aquaporins are membrane intrinsic proteins (MIP) that form pores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…Genes identified in indica regions of IL22 were arbitrarily selected and their expression analyzed by RT-qPCR analysis. They included genes encoding proteins involved in salt stress tolerance (i.e., TF DREB2A, K + efflux 5 transporter, tonoplast intrinsic protein TIP1;1, and Calcineurin B-Like Protein-Interacting Protein Kinase 9-CIPK9) (Liu et al, 1994;Dubouzet et al, 2003;Li et al, 2008;Mallikarjuna et al, 2011;Zhu et al, 2018;Kurowska, 2021;Shabala et al, 2021). RT-qPCR analysis confirmed that indica genes are expressed in leaves of IL22 plants, and also revealed differences in the expression level of these genes between IL22 and its salt-tolerant indica parent FL478 when grown under control conditions (Figure 5, gray bars).…”
Section: Fine Mapping Of Indica Introgressions In Il22 By Transcriptome Genotypingmentioning
confidence: 99%
“…Genes identified in indica regions of IL22 were arbitrarily selected and their expression analyzed by RT-qPCR analysis. They included genes encoding proteins involved in salt stress tolerance (i.e., TF DREB2A, K + efflux 5 transporter, tonoplast intrinsic protein TIP1;1, and Calcineurin B-Like Protein-Interacting Protein Kinase 9-CIPK9) (Liu et al, 1994;Dubouzet et al, 2003;Li et al, 2008;Mallikarjuna et al, 2011;Zhu et al, 2018;Kurowska, 2021;Shabala et al, 2021). RT-qPCR analysis confirmed that indica genes are expressed in leaves of IL22 plants, and also revealed differences in the expression level of these genes between IL22 and its salt-tolerant indica parent FL478 when grown under control conditions (Figure 5, gray bars).…”
Section: Fine Mapping Of Indica Introgressions In Il22 By Transcriptome Genotypingmentioning
confidence: 99%
“… 2016 ; Kapilan et al. 2018 ; Kurowska 2021 ) and future studies may investigate their role in tomato’s response to warm temperature.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the weighted cluster analysis we identified three additional genes belonging to the solute transport category: Solyc03g019820.3.1 and Solyc06g072130.4.1 are tonoplast intrisic proteins, that are involved in transport of water and small molecules across the vacuolar membrane, and Solyc06g051860.3.1 is a PHT1-type phosphate transporter. Aquaporins are known to play an important role in maintaining cell homeostasis under abiotic Stress (Afzal et al, 2016; Kapilan et al, 2018; Kurowska, 2021) and future studies may investigate their role in tomato’s response to warm temperature.…”
Section: Discussionmentioning
confidence: 99%